Endogeneous development: a comprehension of researchers perspective from a federal company - Cruz, Anderson Cougo da; Rios, Silvana Einhardt; Einhardt, Mariani Garcia; Cruz, Franciane Cougo da (Revista de Administração da UFSM, 2016)
The objective of this research was to analyze the understanding and application of the concepts of endogenous development in the context of the Brazilian Agricultural Research Corporation (Embrapa), Pecuária Sul unity in order to ascertain the perception of the researchers of this institution on the importance of endogenous development to obtaining sustainable growth. Specifically, this study highlights the importance of this process, checking the knowledge of researchers in relation to the theme and understanding about the factors that reflect a commitment to the concept of endogenous development. For this, through a case study, exploratory and descriptive, using a qualitative approach and literature analysis, interviews were conducted with 19 researchers who are effective servers in Embrapa Pecuária Sul unity, located in the city of Bagé, Rio Grande do Sul, Brazil. The instrument was composed of seven mixed questions, giving information that was interpreted with the help of content analysis. From this, it as concluded that the company analyzed, based on the understanding of the researchers interviewed, do not realize the endogenous development as the most favorable alternative for sustainable development.